2003
DOI: 10.1248/yakushi.123.1039
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Drug Information Necessity Factor of Generic Drugs

Abstract: The utilization of generic drugs has been promoted, but there is concern about the insu‹ciency of the information provided on generic drugs. To make an objective evaluation of the amount of information supplied by generic drug manufacturers, we tried to quantify the information supply. The information described in the package insert and the interview form were used in the evaluation. We sent a questionnaire to 1000 randomly selected hospitals nationwide to determine the necessity of each information item in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…We previously evaluated information quantities for 15 pharmaceutical ingredients (255 product items) in order to study the present state of generic drug information supply via paper media. 2,3) However, upon determining scores for each piece of information, we found that they did not necessarily re‰ect the necessity of that information in medical care situations. We then conducted a new questionnaire survey of 1,000 medical institutions throughout Japan, revising our evaluation criteria to re‰ect necessity in medical care situations, for the drug information provided.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We previously evaluated information quantities for 15 pharmaceutical ingredients (255 product items) in order to study the present state of generic drug information supply via paper media. 2,3) However, upon determining scores for each piece of information, we found that they did not necessarily re‰ect the necessity of that information in medical care situations. We then conducted a new questionnaire survey of 1,000 medical institutions throughout Japan, revising our evaluation criteria to re‰ect necessity in medical care situations, for the drug information provided.…”
Section: Introductionmentioning
confidence: 86%
“…We then conducted a new questionnaire survey of 1,000 medical institutions throughout Japan, revising our evaluation criteria to re‰ect necessity in medical care situations, for the drug information provided. 4) In this report, we present the results of an objective evaluation of the quantities of generic drug information provided by paper media, based on these new evaluation criteria.…”
Section: Introductionmentioning
confidence: 99%